Standardizzazione e validazione dei dati della pianificazione urbanistica locale nella regione del Veneto - Tomaello, Francesco; Favaretto, Mario; Fiduccia, Andrea (GEOmedia, 2013)
La Legge Regionale del Veneto n. 11 del 23 aprile 2004 ha introdotto varie innovazioni, tra cui l'obbligo per i Comuni di compilare in formato digitale i propri strumenti urbanistici, ed in particolare i Piani Regolatori Comunali, secondo una specifica di compilazione predisposta dalla stessa Regione, che prevede in particolare anche l'obbligo di usare un formato GIS standardizzato. According to the Land Planning Act of Region Veneto (Italy), Municipalities have to compile their Local Land Plans (PRC – Piani Regolatori Comunali) using a standardized GIS data model. The Region Veneto has issued such specifications about the GIS data model immediately after the entry into force of Law n. 11 (2004). The Veneto Region has immediately activated a system for the validation of the GIS data of Plans coming from Municipalities. The system computes two indices to measure the compliancy of the incoming data with the data model according to art. 11 of Law n. 11 (2004). For sure the operative model issued by the Law n. 11 (2004) requires skilled technicians both from the side of the Municipalities for the population of the geodatabase of the local land plan and from the side of the Veneto Region for the validation. The Veneto Region has set up a specific office staffed with GIS skilled personnel using a state-of-the-art software procedure for data validation. The workflow of data validation has been published by the Region in January 2007. The latest and improved release of GIS data model was issued in January 2010. The software procedure has been built on top of Intergraph's GeoMedia GIS software. Currently the whole procedure for Local Land Planning is coherent with the SDI of Region Veneto - operative since 2011. According to INSPIRE Directive and some italian laws, Region Veneto has started the design of the new workflow for the GIS component of local land planning. The leading concepts is the Municipalities will be capable of validating autonomously their GIS datasets using a web service so the data uploaded by Municipalities into the Central GeoDatabase of Region Veneto's SDI will be ready for automated mosaicking , remodelling (using local data models and INSPIRE Land Use data model) and SDI-sharing.